ANALISIS DUKUNGAN ORANG TUA TERHADAP PROGRAM PEMBERIAN TABLET TAMBAH DARAH REMAJA PUTRI - Dwiyana, Parlin; Angesti, Annisa Nursita; Prikhatina, Ratih Agustin; Kharisma, Kharisma; Salsabila, Dhea Marliana (Program Studi Ilmu Gizi, Jurusan Kesmas Fakultas Ilmu-Ilmu Kesehatan Universitas Jenderal Soedirman, 2024)
Adolescent girls are a group that is vulnerable to experiencing nutritional problems such as anemia, which is characterized by hemoglobin levels in the blood that are lower than normal. Factors that support compliance with the consumption of blood supplement tablets in adolescent girls include perception, knowledge, motivation, attitudes, and family and teacher support regarding anemia and blood supplement tablets administration. This research aims to determine the relationship between the knowledge and characteristics of parents on parental support in implementing the blood supplement tablets program for adolescent girls. This research used a cross-sectional design located at MAN 3 Jakarta with 96 parents of adolescent girls as respondents. Data were analyzed using the Chi-Square test. The results showed that there was a relationship between the father's occupation and parental support (p=0.005), the father's income and parental support (p=0.000), the father's education and parental support (p=0.006), the mother's education and parental support (p=0.000), and parental knowledge with parental support (p=0.001). Thus, the father's occupation, the father's income, the father's education, the mother's education, and parental knowledge are factors related to parental support for the blood supplement tablets program for adolescent girls